A systematic review of the concentration of bacteria in daycare centers (DCCs) - N. F. A., Azman; Norhidayah, Abdull; M. K., Mokhtar; Z., Shahri (Penerbit Universiti Malaysia Pahang, 2023)
Microbes in indoor buildings have gotten a lot of interest from the scientific community and the public because of their direct relationship to human health. However, there is still a shortage of thorough data on bacterial concentration in daycare centers air. This research systematically reviews the influencing factor of bacteria growth, the concentration of bacteria and proposes a further research direction. The research article was selected from year 2011 to 2022, 11 original research that met the qualifying criteria were assessed in the major databases. The highest indoor bacteria content was identified in a study from Portugal (5256 CFU/m3), while the lowest was found in an Iranian study (453.93 CFU/m3). The concentration of bacteria indoors are varies in different seasons and the higher indoor bacteria concentrations were found in winter and spring seasons. In addition, researchers also find a positive correlation between bacterial growth with the exposure of particulate matter (PM1, 2.5, PM10). This review reveals that a short sampling period is not enough to explain and evaluate the concentration of bacteria in daycare centers. Thus, research suggests that further research be done on bacteria exposure in daycare centers because it can raise awareness among parents and staff about the need for clean air for children and provide ideas for improving daycare facilities.